ANALYZING CHARACTERS IN THE FILM MOANA: AN EXPLORATION OF LEADERSHIP VALUES AND CULTURE IDENTITY - Eripuddin; Pipit Rahayu; Siti Aisyah; Azi Nurazima Juhastri (English Study Program University of Pasir Pengaraian, 2025)
This study analyzes leadership values and cultural identity in the animated film Moana (2016) through the main characters. Using qualitative descriptive research, it explores how leadership and cultural identity are depicted in character development, dialogue, narrative, and visuals. The primary data source is the film, focusing on Moana, Maui, and Chief Tui, who represent leadership practices and cultural meanings. Data were collected through repeated viewing of the film, selecting relevant scenes and dialogues, and analyzed with thematic analysis. The findings reveal that leadership in Moana is portrayed as a value-based, culturally grounded process rather than authority. Moana demonstrates leadership values such as responsibility, courage, perseverance, empathy, and commitment to community. Leadership is deeply connected to Polynesian traditions and values, showing the influence of culture and nature. The contrasting portrayals of Maui and Chief Tui highlight leadership as a dynamic, transformative process that involves balancing tradition and change. The study concludes that Moana promotes ethical leadership and cultural awareness.